Supercritical CO2 extraction of Moroccan argan (Argania spinosa L.) oil: Extraction kinetics and solubility determination. Issue 46 (April 2021) - Mouahid, Adil; Bombarda, Isabelle; Claeys-Bruno, Magalie; Amat, Sandrine; Myotte, Emmanuelle; Nisteron, Jean-Paul; Crampon, Christelle; Badens, Elisabeth
Graphical abstract: Highlights: The extraction kinetics of argan oil extracted using supercritical CO2 were reported. The effects of particle size diameter and roasting on extraction kinetics was investigated. Sovova's BIC mathematical model was applied for a better understanding of the mechanism of extraction kinetics. Argan oil solubility in supercritical CO2 was determined and modelled using Chrastil equation. Abstract: Experimental and modelling investigations of supercritical CO2 extraction of oil from Argania spinosa L. kernels were conducted at pressure range from 200 to 400 bar, temperature range of 313–333 K at a CO2 flow rate of 0.14 kg/h. Regardless of the pressure and the temperature, the highest achievable yield was estimated at 0.63 kgoil / kgbiomass . The extraction kinetics were modeled with Sovová's broken and intact cells model. The extraction of type B was found to be the most suited extraction type. Argan oil solubility in supercritical CO2 was determined and modelled with the Chrastil equation. A retrograde solubility behaviour was observed at 200 bar and the faster extraction kinetics were found at 400 bar and 333 K. The total tocopherols concentration was found between 389.7 and 1688.6 mg/kgextract . Experiments were performed on unroasted and roasted kernels.